2023
DOI: 10.3390/diagnostics13020205
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition to Define Prognosis of Cancers Treated by Anti-Angiogenic Drugs

Abstract: Background: Body composition could help to better define the prognosis of cancers treated with anti-angiogenics. The aim of this study is to evaluate the prognostic value of 3D and 2D anthropometric parameters in patients given anti-angiogenic treatments. Methods: 526 patients with different types of cancers were retrospectively included. The software Anthropometer3DNet was used to measure automatically fat body mass (FBM3D), muscle body mass (MBM3D), visceral fat mass (VFM3D) and subcutaneous fat mass (SFM3D)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…This evidence allow us to believe that BIA is an effective diagnostic and prognostic tool [ 43 ]. On the other hand, it is also reported that there is a close relationship between osteoporosis and coronary artery calcification, indicating osteoporosis as a predisposing factor for cardiovascular disease [ 44 ]. In this context, the role of BIA clustering results becomes important as a prognostic factor in many different diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence allow us to believe that BIA is an effective diagnostic and prognostic tool [ 43 ]. On the other hand, it is also reported that there is a close relationship between osteoporosis and coronary artery calcification, indicating osteoporosis as a predisposing factor for cardiovascular disease [ 44 ]. In this context, the role of BIA clustering results becomes important as a prognostic factor in many different diseases.…”
Section: Discussionmentioning
confidence: 99%